The Formation of Polar Disk Galaxies - Brook, Chris B; Governato, Fabio; Quinn, Thomas; Wadsley, James; Brooks, Alyson M; Willman, Beth; Stilp, Adrienne; Jonsson, Patrik (The Astrophysical journal, 2008)
Polar ring galaxies, such as NGC 4650A, are a class of galaxies that have two kinematically distinct components that are inclined by almost 90 degree to each other. These striking galaxies challenge our understanding of how galaxies form; the origin of their distinct components has remained uncertain and is the subject of much debate. We use high-resolution cosmological simulations of galaxy formation to show that polar ring galaxies are simply an extreme example of the misalignment of angular momentum that occurs during the hierarchical structure formation characteristic of a cold dark matter cosmology. In our model, polar ring galaxies form through the continuous accretion of gas whose angular momentum is misaligned with the central galaxy.